Experience with the dermatology inpatient hospital service for adults: Mayo Clinic, 2000–2010. (16th October 2012) - Storan, E.R.; McEvoy, M.T.; Wetter, D.A.; el‐Azhary, R.A.; Bridges, A.G.; Camilleri, M.J.; Davis, M.D.P.
Abstract Background There is a paucity of medical literature describing the role of dermatology inpatient hospital services for patients with severe dermatologic disease. A diminishing number of US hospitals have a dedicated dermatology inpatient service run by dermatologists. Objectives To describe the role of a dermatology‐run inpatient service in treatment of severe dermatologic disease from 2000 to 2010 at our institution. Methods We studied demographic characteristics, indications for admission and length of stay for the adult (age, >18 years) dermatology inpatient hospital service over the most recent decade. We compared data from the first 5.5 years with the subsequent 5.5 years and with previously published data. Results A total of 1732 patients had 2216 inpatient admissions to the adult service from 2000 to 2010. The mean (SD) age was 61.3 (17.7) years (age range 18–100 years). Median duration of admission was 3 days interquartile range (IQR), 2–5 days. The most common indications for admission were dermatitis (44.2%), psoriasis (17.4%) and cutaneous T‐cell lymphoma (9.2%). We compared admissions from 2000 to mid‐2005 (n = 1260) to admissions from mid‐2005 to 2010 (n = 956). Statistically significant changes included median length of stay (decreased from 4 days [IQR, 3–6 days] to 3 days [IQR, 2–4 days] P < 0.01), admissions for psoriasis (decreased from 20.7% to 13.0%; P < .01) and admissions for dermatitis (increased from 41.6% to 47.6%; P < .01). Conclusion The number of patients admitted and the median length of stay decreased between the 2 periods. Indications for admission have changed significantly across the two time periods.